Association between the subchondral bone plate and articular cartilage thickness during the progression of osteoarthritis in Dunkin Hartley guinea pigs - Md Yusof, Nur Azirah; Talib, Ain Aisyah; Akman, Akma Azmiera; Zamli, Zaitunnatakhin (Universiti Putra Malaysia, 2017)
Osteoarthritis (OA) is a progression of degenerative joint disease which can cause disability. Previous study shown that thickness of subchondral bone plate (Sbp), trabecular bone (Tb) and calcified cartilage (CC) increases along the progression of OA. However, none of these studies provide evidence of their association, especially during early stage of OA. Thus, this study aims to determine the association between the CC and Sbp thickness during the development of OA in Dunkin Hartley (DH) guinea pigs. Micro-computed tomography (Micro-CT) analyser software was used to measure the Sbp thickness (Sbp Th) in medial and lateral side of DH tibia at 10, 20 and 30 weeks of age. Histological analysis was used to determine the thickness of CC, uncalcified cartilage (unCC) and total articular cartilage (AC), and assess severity of the AC degeneration. The results showed that the Sbp [Medial, p = 0.001; Lateral: p = 0.001] and CC [Medial, p = 0.013; Lateral, p = 0.005] was thicker, but the unCC [Medial, p = 0.004; Lateral, p = 0.004] was thinner, in the medial than lateral side of DH tibia at all time points. In the medial side, a significant increase of Sbp Th and CC Th was observed between 10 and 20 weeks of age [(Sbp Medial, p = 0.01; Sbp Lateral, p = 0.01), (CC Medial, p = 0.045; CC Lateral, p = 0.014)]. In contrast, the unCC thickness was decreased with ageing. Since these changes were significantly associated with the AC degeneration, it may suggest that these events play an important role during the initiation and progression of OA.